Political philosophy - Simmons, A. John (New York : Oxford University Press, 2008)
The most recent addition to the Fundamentals of Philosophy Series, Political Philosophy is a concise yet thorough and highly engaging introduction to the essential problems of the discipline. Organized topically and presented in a straightforward manner by an eminent political philosopher, A.
John Simmons, it investigates the nature and basis of political authority and the structure and organization of political life. Each chapter focuses on a central problem, considers how it could be addressed, and outlines the various philosophical positions surrounding it. Covering both historical
and contemporary work, this unique text offers a survey of major concepts and debates while also reflecting the author's views and contributions. Accessible to novices yet also useful for advanced students, Political Philosophy presents a unified and accessible portrait of the issues that have been
puzzling political philosophers for years.
1. Morals and politics
2. States?
3. Obligations
4. Justice
5. Democracy
6. The world of states.
Bibliografske bilješke na kraju teksta.
Kazalo
Keywords: Filozofija politike -- Demokracija; Moral -- Pravda